Centralized crypto exchanges (CEX) website - Gan, Hing Long (2023)
Digital assets such cryptocurrencies are becoming a trend in the trading scene in these recent years. The more well-known cryptocurrencies among traders are Bitcoin, Ethereum, Ethereum 2, BNB, XRP, and Dogecoin. As a result, it is not surprising that websites dedicated to offering trading services for cryptocurrencies have appeared. Centralized cryptocurrency exchanges (CEX) websites are the name given to these types of websites. The best place for people to buy or sell bitcoins is on CEX websites. Unfortunately, these websites nevertheless show some limitations that will turn away visitors. One of these problems is the long period of waiting time for transactions to be completed. This may happen due to the high volume of trading activities in the websites. Besides, Malaysian users also faced problems with the availability of CEX websites in the country and the lack of accessibility of Malaysian Ringgit in existing CEX websites. To overcome the weakness present in existing CEX website, this project dedicated itself to develop an improved website that will use MYR as main fiat currency for trading and made available for Malaysian to use. Laravel framework will be used in this project for the development of the CEX website. Iterative methodology is used in this project to ensure continuous improvement of the project can be achieved. By following this methodology, a high-quality CEX website can be developed. The outcome of this project is increasing the interest of Malaysian to use CEX website since MYR is made available in the developed website.